Unlearning Aesthetics: Pedagogy and the Perceptual Ecology of Class Struggle - Ford, Derek R.; Chaparro, Daniela (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
Materialist approaches to aesthetics historicize our sensuous capacities, orientations, and objects by attending to their ongoing production. This article begins by articulating capital not as an “economic” system but as a broader perceptual ecology that produces particular correspondences between subjects and the world. In response to the clear limits of ideology critique we argue that not only is capitalist ideology reproduced educationally but that pedagogical challenges to capital need to generate experiences with alternative collective perceptual realities that exist in the present. In our current conjuncture, such experiences are political insofar as they help rejuvenate the belief in the possibility and reality of revolutionary transformation. We offer the pedagogy of unlearning as one potential educational philosophy and practice that interrupts our inauguration into capital’s sensuous regime. Moreover, we read Marx’s Capital as a text that is guided by an aesthetic pedagogy to help us understand capital as a totality in shifting and partial ways and that, more importantly, produces a gap in the reader between our presumed sensuous certainty and other possible perceptual configurations.